PENINGKATAN NILAI TAMBAH KOMODITAS PERKEBUNAN PETANI KOPI ORGANIK DI DESA SRIMENANTI LAMPUNG BARAT - Achyani Achyani; Agus Sutanto; Eva Faliyanti (Ethos: Jurnal Penelitian dan Pengabdian kepada Masyarakat, 2018)
West Lampung Regency is a regency in Lampung Province with the main livelihood of its people as farmers. West Lampung regency has plantation area of 65,211.8 Ha with three superior commodities namely robusta coffee, pepper and cocoa. Nationally, coffee, pepper and cocoa commodities are also national commodities whose production increase will be prioritized for the purpose of foreign exchange earnings / exports. Srimenanti village is one of the villages in the subdistrict of Air Hitam, with land area for settlements, plantations, and rice fields. The selection of Desa Sri Menanti because this village has potential for plantation and has potential for the development of plantation products in order to increase the capacity and economy of the community, but also the community is warm to receive renewal in terms of environmentally friendly technology. Increased farmers' income, especially coffee cultivators do not seem to be able to improve welfare. This is because coffee farmers just sell their products to distributors. Strategic efforts of all stakeholders are needed to increase the income of existing coffee farmers and develop enough in Lampung. The prospect of plantation commodity is very big, processed into canned food such as organic coffee powder, organic coffee powder with additional fruit flavor, durian, stroberry and others, various processed banana chips, jam etc. Products from vegetables such as dodol squash, tomato dodol. This is so that all existing potentials can be managed to the maximum and boost the economy and progress of this village.